Lichens in South Greenland. - Hansen, Kjeld (Meddelelser om Grønland, 1971)
In 1962 and in 1965 a total of 2,000 collections of 126 species of macrolichens was made in two areas in South Greenland; quantitative investigations of the species' occurrence and distribution were also carried out. Uniform investigations were made at 8 and 7 stations, respectively, whose climate can be characterized on the basis of meteorological observations as, respectively, relatively continental, sub-continental, sub-oceanic or oceanic. Information is provided concerning the occurrence and frequency of the 126 species in the areas of investigation in relation to climatic conditions. A survey based on these investigations is given as follows: 1) the number of species at stations having various climates; 2) the quantity of terricolous, saxicolous and corticolous lichens at difTerent stations; 3) the most common species. The 126 species are divided on the basis of their distribution in Greenland into 4 types: distinctly southern, somewhat southern, widely distributed and somewhat northern species. On the basis of their distribution in South Greenland in relation to continentality or oceanity the species also are divided into 4 types: distinctly continental, somewhat continental, indifferent, and somewhat oceanic species. The distribution of the species in 13 of the 16 possible combinations of the two abovementioned groups of types of distribution is also surveyed. A correlation between the vertical and horizontal distribution in Greenland is shown.